Analysis and Implementation of a Fast Corner Detector on Image Stitching in the Formation of Aerial Photogrammetry Images - Lukmana Sardi, Indra; Yulianto, Fazmah Arif; Sthevanie, Febryanti (International Journal on Information and Communication Technology (IJoICT), 2024)
Aerial Photogrammetry is one of the products from the fields of geography in taking the object, area, or phenomenon on the surface of the earth. Using kamera with a photographic recording process and by the help of a detector in the form of film. In the application, required proper technique in merging images of aerial photographs in order to gain a broader perspective. In this final project, stitching method used in order to merging the images. Image stitching is a method for combining multiple images with overlapping fields of view to produce a panoramic image or picture, the image has a wider viewing angle. Image stitching takes some of the features of the image as a reference in merging overlapping areas, it's named FAST corner detector. The results suggest that the FAST corner detector with a threshold n = 9 appropriate if used in image stitching process that resulted in three classes based on the panoramic image of the cross correlation results, which is the upper class (cc>0.9) on the image with stitching horizontal, diagonal and vertical, the medium class (0.8<cc<0.9) on the image with stitching involves rotation and the lower class (cc <0.8) on a stitched image with scale.